TRANSFORMATION OF TEACHER ROLES: ADDRESSING DISRUPTIONS IN EARLY CHILDHOOD EDUCATION - Putra, Windisyah (Proceeding International Seminar of Islamic Studies, 2024)
The era of disruption in early childhood education (ECE) poses significant new challenges for educators. This study analyzes the transformation of the teacher's role in dealing with technological dynamics and rapid societal changes. The primary focus is on exploring adaptive strategies applied by teachers to sustain their relevance in delivering effective and meaningful learning. The literature review method engages various sources related to the transformation of the teacher's role in addressing disruptions in early childhood education. The research findings highlight: firstly, the importance of enhancing digital competence as a key step in supporting the teacher's existence; secondly, the necessity of collaboration among teachers, parents, and other education stakeholders to create a holistic learning ecosystem; thirdly, integrating more cutting-edge technology will make teachers more creative in designing their lessons; and fourthly, the need for an approach that encompasses technological aspects, pedagogical skills, and personal development of teachers. This study contributes to the early childhood education literature by providing a profound insight into the teacher's role in facing disruption and laying the foundation for the development of more effective education policies and practices in the future.